(untitled) (Research, Society and Development, 2021)
Problems involving oral health, including periodontal disease, have been increasingly recognized as important precursors of negative consequences on the performance of daily activities and on the quality of life of individuals. This fact becomes even more relevant when it comes to the health of pregnant women and the developing fetus that may be born prematurely or with low birth weight. The objective of this review is to evaluate the interrelationship between periodontal disease and pregnancy, characterizing its association with dental prenatal care and baby’s health. This is a narrative review of the literature, aiming to identify the factors associated with dentistry and dental prenatal care. Articles published in the last ten years and available in English and Portuguese were included using the keywords dentistry and pregnancy; dentistry and dental prenatal care; dentistry and prenatal and periodontal diseases. It was concluded that maternal oral health influences directly their own health, but also the baby’s health. Thus, the importance of performing dental prenatal care to prevent oral and systemic pathologies is notorious, as well as preventing premature and low birth weight deliveries.